ENGLISH LANGUAGE LEARNING AND TEACHING USING KAHOOT - Ludovikus, Ludovikus; Sabarina Panjaitan, Ribka; Mailintina, Yurita; Sudirman, Anselmus (Jurnal Muara Pendidikan, 2024)
Globalization and the growth of technology have brought everyone a deep attachment to all human life and contexts. That situation also leads to a change toward using learning media and instruments that are more adaptive, especially in making the information obtained accessible. The research method used is a quantitative descriptive analysis method. The tool used is a descriptive analysis using the IBM SPSS 20.0 version. The result showed that the majority of respondents (58.9%) agreed with the effectiveness of Kahoot in English teaching and learning. This suggests that many students perceive Kahoot positively as a tool for enhancing their English language skills. However, other respondents (41.1%) expressed disagreement with the effectiveness of Kahoot in English teaching and learning. In conclusion, the data presented offers valuable insights into students' perceptions of English teaching and learning using Kahoot. While most students agree with its effectiveness, a significant minority hold differing views. Understanding and addressing these varied perceptions are crucial for optimizing Kahoot and similar tools in language education, ultimately enhancing student engagement and learning outcomes.